Misuse of the Function of the Government's Cash Social Assistance Program (BST) During the Covid-19 Pandemic - Endah Ratnawaty Chotim (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
The purpose of this study is to find out the obstacles in the process of implementing cash social assistance in Simpang Village, Pasirkuda District, Cianjur Regency, to find out the latent and manifest functions of Cash Social Assistance (BST), to find out the forms of abuse from the recipient community of Cash Social Assistance (BST) in Simpang Village, Pasirkuda District, Cianjur Regency. This study used a qualitative approach with a descriptive method used by analyzing and describing events at the research location. The results of this study indicate that the distribution of Cash Social Assistance (BST) has been distributed to communities affected by the Covid-19 pandemic. However, there was misuse in the utilization of Social Cash Assistance (BST) funds by some beneficiary communities in Simpang Village. This is a latent function found in this study. In addition, the reality of the community's dependence on Cash Social Assistance (BST) in Simpang Village which can result in a feeling of laziness, consumptive community behavior and the community becoming not self-sufficient.